Implementasi Zero Wrap Menggunakan Kain Linen Dengan Teknik Zero Waste: Teknik Zero Waste - Mulyani Gayuh; Wahyuningsih Urip (Pusat Penerbitan LPPM ISI Bali, 2026)
The increasing volume of single-use packaging waste has become one of the major environmental challenges receiving global attention. Plastic and paper packaging materials that are used for a short period significantly contribute to waste accumulation and environmental pollution. This study aims to explore the implementation of zero wrap using linen fabric through a zero waste approach as an alternative sustainable packaging solution. The research employed an applied experimental method by implementing two wrapping techniques, namely the mummy wrapping technique and the Japanese traditional furoshiki method. Linen fabric was selected as the primary material due to its durability, strength, reusability, and biodegradable properties. The research process included concept and material exploration, application of wrapping techniques to objects of various shapes and sizes, visual observation, documentation, and evaluation based on material efficiency, wrapping strength, ease of use, aesthetic value, and environmental sustainability. The results indicate that linen fabric effectively supports the implementation of the zero wrap concept without generating material waste during the wrapping process. The mummy technique produced a stable wrapping structure capable of adapting to various object forms, while the furoshiki technique demonstrated greater flexibility and provided a more decorative and artistic visual appearance. In addition to its protective function, linen-based packaging offers aesthetic value and the potential for repeated use in different contexts. The study concludes that the implementation of zero wrap using linen fabric represents a sustainable packaging solution that successfully integrates functional, aesthetic, and environmental aspects while supporting the principles of the circular economy and zero waste design in contemporary packaging practices.